Analisis Kritik Sosial dalam Novel Sapa Bilang Pelaut Mata Keranjang Karya Safar Nurhan - Hasanah, Uswatun; Nama, I Ketut; Waluyo, Isnan (CV. Eduartpia Publisher, 2025)
This research was motivated by the author's interest in literary works, particularly Safar Nurhan's novel Sapa Bilang Pelaut Mata Keranjang, which depicts the social life of coastal communities. The purpose of this research is to analyze and reveal the author's social criticism of the social reality in Safar Nurhan's novel Sapa Bilang Pelaut Mata Keranjang. This novel represents various social issues that occur in coastal communities, such as economic inequality, weak village government bureaucracy, and law enforcement in cases of sexual violence. This study uses a qualitative descriptive method with Ian Watt's sociological approach to literature, which views literary works as a mirror of society. Data collection techniques were carried out through close reading and literature study, while data analysis was conducted by interpreting texts containing social criticism. The results of the study show that the author conveys sharp criticism through the dialogue and narration of characters that describe social inequality and injustice in coastal communities, including social and economic criticism, criticism of bureaucracy and government, and criticism of law enforcement. Thus, this novel not only serves as entertainment but also as a medium for social criticism that reflects the reality of society.